Analisis Praktik Esg Bank First Mover on Sustainable Finance - Pangaribuan, Clara Marshella Pitauly; Idrianita, Idrianita (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
In the era of globalization and digitalization, attention to Environmental, Social, and Governance (ESG) issues has become increasingly relevant in the banking sector. OJK Regulation No. 51/POJK.03/2017 encourages banks to consider ESG aspects in their operations, aligning with Indonesia's commitment to sustainable development goals. This study explores the implementation of ESG among first mover banks through the Triple I approach (Intention, Integration, Implementation) and its impact on financial performance and bank reputation. A quantitative descriptive method was employed using secondary data from the annual reports of first mover banks listed on the Indonesia Stock Exchange (2019-2023). The results indicate a strong commitment to sustainability, ESG integration in operations, and tangible implementation efforts. Positive impacts include increased profitability, enhanced reputation, higher customer loyalty, and reduced reputational risks. First mover banks can lead in sustainability, delivering positive outcomes for society and the environment while enhancing financial performance.